The Secret of Healing in the Use of Assisted Reproductive Technologies and Fundamentals of Security of Information - Kasimova Zumrad Rakhmatovna (Genius Journals, 2023)
This article provides a comparative analysis of adoption and the use of assisted reproductive technologies. The preservation of information about the birth of a child using assisted reproductive technologies through medical secrecy will be considered. It is analyzed in which cases such information can be disclosed. The types of responsibility for disclosing medical confidentiality will be considered, as well as proposals and recommendations for improving the legislation on medical confidentiality and confidentiality of information, which is special in relation to information about the origin of children when using ART, will be made.
Keywords: adoption; assisted reproductive technologies; secret of adoption; secret of origin when using assisted